Feasibility Study of Integrating Absorption Heat Pump into Methanol Steam Reforming Process for Hydrogen Production - Willy Yanto Wijaya; Ken Okazaki; Kazuyoshi Fushinobu; Abdul Waris (Indonesian Journal of Physics, 2007)
Theoretically, Methanol Steam Reforming (MSR) process to produce hydrogen only requires endothermic heat with temperature lower than 100°C. Meanwhile, waste heat in the temperature level of 100-150°C is disposed in huge amount by various industrial sectors every year. If this abundant waste heat can be recovered and stored into hydrogen energy through the MSR, a potential gain and high-efficient energy system could be achieved. However, empirically, temperature level ≥ 200°C is required for the MSR process to have high conversion from the methanol to hydrogen. Therefore, Absorption Heat Pump (AHP) system is then utilized to enhance the temperature level of the waste heat. Nevertheless, AHP system certainly requires additional input energy. This research was to investigate the feasibility of integrating the AHP system into MSR process to produce hydrogen. Further consideration on hydrogen to electricity conversion using Fuel Cell (FC) would also be provided. The feasibility study was conducted through the efficiency calculations, either for energy or exergy terms, for several theoretical as well as actual-approximation cases.